A new approach to fabricate agarose microstructures. (9th July 2013) - De Maria, Carmelo; Rincon, Julio; Duarte, Alonso A.; Vozzi, Giovanni; Boland, Thomas
<x xml:space="preserve">Abstract</x> Agarose hydrogels find wide applications in different fields such as biological sciences, tissue engineering and food industry, and its use has been investigated in many fields ranging from electronics to crystallography. Usually, agarose structures are made by casting, and more recently some attempts have been made to build agarose structures by additive manufacturing. All of the fabrication methods are based on thermo‐reversible gelling properties of agarose gel. A new method to fabricate agarose microstructures in a binary solvent composed of water and dimethyl sulfoxide is presented and modelled in this paper. This new method allows building agarose structures by an additive layer‐by‐layer approach using a modified inkjet printer. The fabrication method and printing device are described in detail. Furthermore, finite‐element model simulations, which predict with high confidence the final line width of the printed structures, are discussed and analysed. Mechanical properties of printed gel structures are comparable with those obtained by gel casting, as demonstrated by tensile testing. The presented results demonstrate the feasibility of this approach to fabricate agarose structures with more complex shapes that can be done by casting. Copyright © 2013 John Wiley & Sons, Ltd.